«The Easter World» of Nicholas II during the Bell for Witte Tolled - Nelly Mikhailovna Tairova (Управленческое консультирование, 2018)
Nicholas II tried to keep the state order existing at his father Alexander III, however the first years of his board were marked by acute shortage of activity of the government. Many years only the Ministry of Finance led by S.Yu. Witte successfully functioned. Nicholas II has paid the attention to activity of the Ministry of Foreign Affairs and together with the minister, M.N. Muravyyov initiated in 1899 convocation of the International Hague conference of the world for carrying out peace policy in Europe. Through the Ministry of Internal Affairs, there was a transformation of the political relations between autocracy and the public towards liberalization (search of new forms of interaction of government institutions of management to territorial institutions). S.Yu. Witte and Nicholas II’s relationship is a ball of moral, ethical, political and economic relations, despite a difference in views, for both in the center of their interests there was a State and Autocracy.